1994
DOI: 10.1007/bf02059887
|View full text |Cite
|
Sign up to set email alerts
|

Plant response to eggs vs. Host marking pheromone as factors inhibiting oviposition byPieris brassicae

Abstract: Pieris brassicae L. butterflies secrete miriamides onto their eggs. These avenanthramide alkaloids are strong oviposition deterrents when sprayed onto a cabbage leaf. However, these compounds could not be detected in cabbage leaves from which egg batches had been removed two days after deposition and that still showed oviposition deterrency. It was concluded that the miriamides were not directly responsible for the avoidance by females of occupied leaves while searching for an oviposition site. Evidence was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…In Pieris brassicae, for example, it was long believed that a MP was employed by females in order to discriminate among hosts (Rothschild & Schoonhoven, 1977;Schoonhoven et al, 1981). Recent work, however, has shown that the host plant itself responds to the presence of P. brassicae eggs and that systemic changes in leaf surface chemistry may be the primary source of an oviposition-deterring effect (Blaakmeer et al, 1994). Is release of such compounds evidence of an active process that evolved to serve the function of assessment of conspecific brood?…”
Section: Cues Versus Signals In Assessment Of Brood Presencementioning
confidence: 99%
“…In Pieris brassicae, for example, it was long believed that a MP was employed by females in order to discriminate among hosts (Rothschild & Schoonhoven, 1977;Schoonhoven et al, 1981). Recent work, however, has shown that the host plant itself responds to the presence of P. brassicae eggs and that systemic changes in leaf surface chemistry may be the primary source of an oviposition-deterring effect (Blaakmeer et al, 1994). Is release of such compounds evidence of an active process that evolved to serve the function of assessment of conspecific brood?…”
Section: Cues Versus Signals In Assessment Of Brood Presencementioning
confidence: 99%
“…In honour of Miriam Rothschild they were named miriamids (Blaakmeer et al, 1994b). However, when Blaakmeer et al (1994a) tested how females of P. brassicae accept cabbage leaves from which conspecific eggs had been removed, they noticed that these leaves were also avoided for egg deposition even though no eggs were present anymore. Oviposition-deterring activity was also observed in leaves without eggs, but adjacent to those carrying eggs, indicating a systemic effect.…”
Section: Formation Of Neoplasmsmentioning
confidence: 99%
“…Since Blaakmeer and co-workers did not detect the above mentioned oviposition deterring components of the eggs on the leaves from which the eggs had been removed, they concluded that the leaves themselves had produced deterrents in response to the egg deposition. And indeed, oviposition deterring components could be extracted from leaves of Brassica oleracea from which eggs had been removed by briefly dipping the leaves into methanol (Blaakmeer et al, 1994a). Thus, the oviposition deterrents of cabbage leaves produced in response to the egg deposition of P. brassicae are most likely present on the surface of the leaves.…”
Section: Formation Of Neoplasmsmentioning
confidence: 99%
“…Plant responses may be more adaptively variable than is commonly considered. After all, the ample evidence on responses of plants to competitors, herbivores, and pathogens (Blaakmeer et al, 1994;Bruin et al, 1995;Karban & Baldwin, 1997;Shulaev et al, 1997;Ballaré, 1999) should make us careful not to underestimate the potential of plants to respond to biotic components of the environment.…”
Section: Responses Of Herbivores To Induced Plant Volatilesmentioning
confidence: 99%